DISCOVERI-INQUARY METODE YANG DIPAKAI YESUS DALAM KISAH PENGAKUAN PETRUS (MATIUS 16:13-20) - Marlen Tineke Alakaman (IAKN Ambon, 2018)
Teaching by using innovative and even innovative methods will help children to more quickly understand, understand and be able to analyze the story or teaching materials in every learning process. The Narrative of Peter's Confession in Matthew 16: 13-20, there are plans and ways that Jesus used as the Great Teacher called learning methods for preaching or teaching about the Kingdom of God. It is undeniable that in the reality and experience of teaching Jesus according to the testimony of the Synoptic Gospels that Jesus used the method or way to teach, but in this text the author gets a new or another method of Discovery and Inquary that is highly relevant to the use of teaching methods for teachers, to improve children's intelligence as well as demonstrate high analytical skills in children as well as enhance a fun learning environment in the classroom.